2016
DOI: 10.3389/fpsyt.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Altered SPECT 123I-iomazenil Binding in the Cingulate Cortex of Children with Anorexia Nervosa

Abstract: Several lines of evidence suggest that anxiety plays a key role in the development and maintenance of anorexia nervosa (AN) in children. The purpose of this study was to examine cortical GABA(A)-benzodiazepine receptor binding before and after treatment in children beginning intensive AN treatment. Brain single-photon emission computed tomography (SPECT) measurements using 123I-iomazenil, which binds to GABA(A)-benzodiazepine receptors, was performed in 26 participants with AN who were enrolled in a multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Indeed, it is still not possible to differentiate between GAD from MDD based on a review of a multimodal neuroimaging evidence to date although the same study found a correlation between limbic/paralimbic activity and the combined sample including healthy controls based on levels of general distress [ 60 ]. Of course, similarity between the DSM diagnoses of MDD and GAD and the RDoC constructs of response to Loss and PT do not constitute equivalence, but evidence using POMS:Tension and Depression also suggest a convergence in correlation between PT and Loss on the one hand, and impaired activity of the anterior cingulate cortex [ 61 , 62 ] and amygdala [ 63 ], as well as reduced GABA-A receptor binding in the posterior cingulate cortex and left superior frontal regions [ 64 ] on the other. Increasing evidence that physiological paradigms such as startle response are a reliable differentiator of fear or distress [ 65 ] suggests that a more biologically-grounded conceptualisation of NVS constructs is simply AT vs non-AT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is still not possible to differentiate between GAD from MDD based on a review of a multimodal neuroimaging evidence to date although the same study found a correlation between limbic/paralimbic activity and the combined sample including healthy controls based on levels of general distress [ 60 ]. Of course, similarity between the DSM diagnoses of MDD and GAD and the RDoC constructs of response to Loss and PT do not constitute equivalence, but evidence using POMS:Tension and Depression also suggest a convergence in correlation between PT and Loss on the one hand, and impaired activity of the anterior cingulate cortex [ 61 , 62 ] and amygdala [ 63 ], as well as reduced GABA-A receptor binding in the posterior cingulate cortex and left superior frontal regions [ 64 ] on the other. Increasing evidence that physiological paradigms such as startle response are a reliable differentiator of fear or distress [ 65 ] suggests that a more biologically-grounded conceptualisation of NVS constructs is simply AT vs non-AT.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with weight gain demonstrated increases of tracer binding in the posterior cingulate cortex and occipital gyrus. These findings were interpreted as evidence for decreased GABA(A)-benzodiazepine binding in AN, related to anxiety, which normalizes after successful treatment (Nagamitsu et al 2016).…”
Section: Alterations Of Other Neurotransmitter Systems In Eating Diso...mentioning
confidence: 95%
“…Nagamitsu et al noted the correlation between 123 Iiomazenil binding by cortical GABA receptors and clinical symptoms of anorexia in children [16]. Higher EAT-26 scores were significantly associated with lower GABA iomazenil-binding activity especially in the anterior cingulate cortex.…”
Section: Altered Spect 123 I-iomazenil Binding In the Cingulate Cortementioning
confidence: 99%
“…Nagamitsu i wsp. zwrócili uwagę na współzależność pomiędzy wiązaniem I 123 -iomazenilu przez korowe receptory GABA, a objawami klinicznymi anoreksji u dzieci [16]. Wyższe wyniki w teście EAT-26 oraz zaburzenia nastroju były mocno powiązane z mniejszym wiązaniem hamującym GABA w niektórych regionach mózgu, szczególnie przedniej części zakrętu obręczy.…”
Section: Zmienione Wiązanie I 123 -Iomazenilu W Korze Obręczy U Dziecunclassified